USING ESSENTIAL OILS TO COMBAT THE THREAT OF MULTI-DRUG RESISTANT BACTERIA, PSEUDOMONAS AERUGINOSA - Grullon, Jenies; Mack, James P.; Rojtman, Albert (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The development of antibiotics was a revolutionary scientific discovery and medical advancement that greatly extended the life expectancy of mankind. Through less than 100 y of using antibiotics to treat infectious bacteria, some of these highly adaptive organisms have developed resistance to the drugs. The healthcare field is greatly concerned with the threat of many common infections that have been considered treatable for decades, regaining its ability to be severely fatal; thus, making alternative treatments currently in high demand. This study concentrated on investigating an alternative treatment for a specific gram-negative bacterium, Pseudomonas aeruginosa (P. aeruginosa), a resistance-gaining bacteria that commonly infects hospitalized patients with weakened immune systems and/or open wounds. Methods: Prior to the age of modern medicine, human beings relied on nature for medicinal treatments. In our research, we focused on determining the in vitro efficacy of using the essential oils, cassia and cinnamon bark, their major component, cinnamaldehyde, as well as the major component of manuka honey, methylglyoxal, as an alternative treatment against P. aeruginosa We tested cassia, cinnamon bark, cinnamaldehyde, and methylglyoxal using the Kirby-Bauer disk diffusion method; the diameter of the zone of inhibition for each treated bacterial sample was measured and compared with the standard antibiotic treatments, tobramycin, and amikacin. Results: This study showed that the selected essential oils, cinnamaldehyde, and methylglyoxal were as effective or better in inhibiting the growth of P. aeruginosa compared to the standard aminoglycoside antibiotics. Conclusion: The tested essential oils, cinnamaldehyde, and methylglyoxal may be useful as an alternative treatment for infections caused by P. aeruginosa and may also provide communities where antibiotics are not readily available, a cost-effective way to treat this infectious disease.